Histo-Anatomy and Sonographic Examination for the Retrocalcaneal Bursal Complex: EURO-MUSCULUS/USPRM Approach - Ricci, Vincenzo; Cocco, Giulio; Mezian, Kamal; Chang, Ke-Vin; Tamborrini, Giorgio; Naňka, Ondřej; Özçakar, Levent (Journal of ultrasound in medicine, 2024)
Insertional Achilles tendinopathy is an umbrella medical term referring to pain and swelling on the posterior aspect of the calcaneus. High-resolution ultrasound imaging is commonly used in daily practice to assess the pathological changes of the Achilles tendon, cortical bone of the calcaneus, and soft tissues located inside the retrocalcaneal space to optimize the management of relevant patients. To the best of our knowledge, a standardized ultrasound protocol to evaluate the retrocalcaneal bursal complex is lacking in the pertinent literature. In this sense, our step-by-step sonographic approach is intended to be an easy and ready-to-use guide for sonographers/physicians in daily practice to assess this anatomical complex in patients with Achilles tendinopathy. Needless to say, the peculiar histological features of this V-shaped synovial/fibrocartilaginous bursa surrounding the posteroinferior wedge of the Kager's fat pad and the retrocalcaneal space make the examination challenging.
Keywords: patní kost; Ultrasonography; tendinopatie; ultrasonografie; Tendinopathy; Achilles Tendon; Humans; Achillova šlacha; bursa synovialis; Bursa, Synovial; Calcaneus; lidé